Criterios e indicadores para avaliacao da sustentabilidade de empresa florestal em Tailandia, Para, na Amazonia Brasileira - Pokorny, B.; Bauch, R. (Empresa Brasileira de Pesquisa Agropecuária, 2000)
The initial aim of this study was to contribute to the development of monitoring and auditing instruments for forest enterprises in the Brazilian Amazon, based on criteria and indicators (C&I) to assess sustainability, practicability and viability of C&I depending on the consideration of interest, visions and values of forest stakeholders. The principal idea of the study was to identify differences between four different stakeholder groups (local actors, local government, local manager and researcher) in the evaluation of a set of C&I defined by international researchers during a workshop. These differences would be used as starting points to work out a common list of C&I suitable for monitoring and auditing. An important methodological element was the assessment of the sustainability of a Brazilian timber enterprise by practical application of C&I. The study confirmed the great potential of C&I as tools to assess the sustainability of timber enterprise activities and showed interesting differences between the evaluation of the C&I by the different stakeholder groups. It was clear that for potential users of C&I monitoring and auditing tools, practicability and simplicity were very important, as well as the relation of costs and benefits. The assessment methods had a strong influence on the results of evaluation to facilitate the application of C&I in monitoring and auditing instruments. Future efforts should concentrate on the definition of clearly defined verifiers and assessment methods, as well as the definition of specific recommendation indicated by the evaluation results.